Revisiting the role of a Mufti¯ in the criminal justice system in Africa: a critical appraisal of the apostasy case of Mariam Yahia Ibrahim - Kadouf, Hunud Abia; Oseni, Umar Aimhanosi; Chiroma, Magaji (Universiti Pertanian Malaysia Press, 2015)
The formal dispensation of criminal justice in pluralistic legal systems has continued to generate academic interest in the last few decades. This has always been influenced by the colonial and post-colonial historical legal reforms in the African continent. Islamic law has played a very significant role in the evolution of the modern nomenclature of legal systems of some of African countries, particularly the common law-based jurisdictions. The application of Islamic law, particularly its criminal justice component, was relegated to mere personal matters as part of the colonial baggage, and it has been a struggling to re-assert itself in some North, East and West African countries. This article therefore examines the dynamics of the application of the Islamic criminal justice system in Africa and the role of mufti based on a case study of a recent apostasy case in Sudan. While the case, as well as the decision of the court, cheated a maelstrom of controversy and rekindled the narratives of human rights activists globally on the sacrosanct nature of freedom of religion, Muslim jurists have argued that Islamic law provides punishments for specific offences such as hudud, qisas and diyyah; the rationale behind such punishments is not only to punish the offenders, but also to deter other people from committing the same offence. For apostasy issues, there is a kind of link established between this offence and treasonable felony in Islamic legal discourse, which might warrant capital punishment. Having reviewed these diverse positions, the article finds that Islamic legal principles and maxims contain numerous principles that should guide the judge in arriving at a decision, particularly when it relates to such a serious offence. This is where the mufti plays his role in advising the judge on core issues in a case while taking into consideration the context of each case. In the Sudanese case of Mariam Yahia Ibrahim, the trial judge should have looked beyond the content of the statute by seeking further clarifications from a learned mufti in order to ascertain the social and religious background of the parties involved.